Differentiated instruction for the middle school language arts teacher : activities and strategies for an inclusive classroom - D'Amico, Joan, 1957- 4 0 16; Gallaway, Kate.; 5 (San Francisco : Jossey-Bass, 2009)
Contains modifiable lessonsfor students with various needs on a range of language arts topics, with learning style assessments, over thirty activities, and worksheets.
Collaborating effectively -- Preparing for differentiated learning -- Effective teaching strategies for differentiating instruction -- Written language conventions -- Writing as a process -- Reading skills -- Reading comprehension -- Oral language.
Grades 5-8--Cover.
Includes bibliographical references (p. 179) and index.
Professional;Professional
Keywords: 2 -- 0; 6; Activity programs. -- Language arts (Middle school);Individualized instruction.;Language arts.;Individualized instruction; 20; 2